Mutations in the Drosophila glycoprotein hormone receptor, rickets, eliminate neuropeptide-induced tanning and selectively block a stereotyped behavioral program. - Baker, J.D.; Truman, J.W. (Journal of Experimental Biology, 2002)
Adult insects achieve their final form shortly after adult eclosion by the combined effects of specialized behaviors that generate increased blood pressure, which causes cuticular expansion, and hormones, which plasticize and then tan the cuticle. We examined the molecular mechanisms contributing to these processes in Drosophila by analyzing mutants for the rickets gene. These flies fail to initiate the behavioral and tanning processes that normally follow ecdysis. Sequencing of rickets mutants and STS mapping of deficiencies confirmed that rickets encodes the glycoprotein hormone receptor DLGR2. Although rickets mutants produce and release the insect-tanning hormone bursicon, they do not melanize when injected with extracts containing bursicon. In contrast, mutants do melanize in response to injection of an analog of cyclic AMP, the second messenger for bursicon. Hence, rickets appears to encode a component of the bursicon response pathway, probably the bursicon receptor itself. Mutants also have a behavioral deficit in that they fail to initiate the behavioral program for wing expansion. A set of decapitation experiments utilizing rickets mutants and flies that lack cells containing the neuropeptide eclosion hormone, reveals a multicomponent control to the activation of this behavioral program.